Effectiveness of REAC neuro postural and neuro psycho physical optimization in improving peripheral vasospasm dysfunction: a case report - Bechelli, Fabio (Frontiers in Medical Technology, 2023)
Case report of an elderly male patient 86 years old, suffering from limbpain related to ulcers in the lower limbs resulting from Peripheral arterial disease (PAD). Clinically evaluated with the aid of infrared thermal imaging before, during and after treatment, he was submitted to treatment with neuromodulation protocols with REAC Technology, Neuro Postural Optimization (NPO) and Neuropsychophysical Optimization (NPPO) in association with traditional treatments for PAD. It was followed clinically with the aid of infrared thermal imaging of the lower limbs before, during and after treatment. He had a clinical result with a significant reduction in pain and infrared thermal images with complete revascularization of both feet. Evidencing that the treatment of dysfunctional adaptive responses by managing psychological factors often associated with anxiety, depression and stress performed by the REAC NPO and NPPO protocols can be a useful intervention to improve symptoms of patients with lower limb pain and circulatory disturbances.